2007
DOI: 10.1021/la063289s
|View full text |Cite
|
Sign up to set email alerts
|

A Predictive Approach of the Influence of the Operating Parameters on the Size of Polymer Particles Synthesized in a Simplified Microfluidic System

Abstract: Monodisperse and size-controlled spherical polymer particles were synthesized by in situ photopolymerization of O/W monomer emulsions. Monomer droplets were produced without surfactant or pretreatment at a needle tip in a simplified axisymmetric microfluidic device. The effect of the viscosity of the continuous phase on the particle size was studied. The system operated in the dripping mode, at a low Reynolds number. A dimensionless master curve describes the particle diameter as a function of the needle inner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 44 publications
8
64
0
Order By: Relevance
“…We note strong differences between the breakup of liquid threads in unbounded conditions (Cramer et al 2004;Ganan-Calvo 1998;Utada et al 2005;Serra et al 2007;Zhang and Stone 1997) and in microconfined geometries (Anna et al 2003;Garstecki et al 2004Garstecki et al , 2005bGarstecki et al , 2005cGarstecki et al , 2006Thorsen et al 2001). For example, Cramer et al (2004) reported that in the case of break-up in co-flow of liquids in unbounded conditions a decrease in the value of interfacial tension between the immiscible phases results in the reduction of droplet size.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…We note strong differences between the breakup of liquid threads in unbounded conditions (Cramer et al 2004;Ganan-Calvo 1998;Utada et al 2005;Serra et al 2007;Zhang and Stone 1997) and in microconfined geometries (Anna et al 2003;Garstecki et al 2004Garstecki et al , 2005bGarstecki et al , 2005cGarstecki et al , 2006Thorsen et al 2001). For example, Cramer et al (2004) reported that in the case of break-up in co-flow of liquids in unbounded conditions a decrease in the value of interfacial tension between the immiscible phases results in the reduction of droplet size.…”
Section: Introductionmentioning
confidence: 88%
“…We verified that the Weber number, We = qm 2 l/c, was approximately 0.0015*0.40; since We \ 1 the interfacial tension forces dominate inertia and the capillary number forms the correct dimensionless group for the description of the behavior of our system. We note that the capillary numbers of the droplet and continuous phase, Ca i and Ca o , respectively, are related as (Serra et al 2007). For this experiment, the rate-of-flow-controlled breakup model predicts no variation in the volume of the droplets (since the value of Q o /Q i stays constant), while the shearing mechanism predicts the volume to decrease with the capillary number (with the third power of Ca for breakup in unbounded fluids).…”
Section: Volume Of the Dropletsmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Once droplets are produced they can be solidified using appropriate reactions. UV photopolymerisation is an effective and convenient way to crosslink droplets produced by microfluidic methods using functionalised polymers, [18][19][20] however, limited studies have been performed with hydrogels 21 and fewer again with synthetic or biosynthetic hydrogels. 22 The production of microspheres by coupling microfluidic droplet formation with UV photopolymerisation is a promising technique for use with biosynthetic hydrogel macromers and particularly for use in cell encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…The technique can be applied for the two-step synthesis of Au/Ag core/shell nanoparticles with high homogeneity [19] and for the hydrothermal continuous-flow synthesis of ZnO micro-and nanoparticles [20]. On the other hand, the application of microfluidic devices with coaxial arrangements of fluid channels and flow-focusing allows the preparation of different kinds of polymer particles with very high reproducibility [21,22].…”
Section: Introductionmentioning
confidence: 99%